Safety and health for construction workers in bridge construction / Muhamad Ekwan Haniffah Baharudin and Syarifah Nur Nazihah Syed Jamalulil - Baharudin, Muhamad Ekwan Haniffah; Syed Jamalulil, Syarifah Nur Nazihah (2018)
A bridge is a structure built to span physical obstacles without closing the way underneath such as a body of water, valley, or road, for the purpose of providing passage over the obstacle. However, there are many risks in constructing a bridge. The aim of this research is to identify the safety and health of construction workers in bridge construction. The objective of this research is to determine the worker's level of awareness on safety and health in bridge construction, to identify the main safety precautions taken by the construction workers in bridge construction and to determine the major barriers faced to implement safety and health in bridge construction. Review of literature was conducted and a questionnaire survey was used to obtain the information needed. A total of 100 questionnaires was distributed and 60 only respondents are responding to the survey. The distribution involved all the worker that works on the bridge construction site in Pasir Mas, Kelantan. The data were analyzed by using the SPSS software with Average Index. The findings indicate that most of the construction workers are aware that safety and health practices on site are important to achieve zero accident and death on site. This study will help the construction workers to Have a clearer exposure on the safety and health practices in the bridge construction site.